Hubungan antara Pemenuhan Kebutuhan Psikologis dengan Perilaku Agresi pada Anak Jalanan - Sandy Nurhuda; Nur Aziz Affandi; Tatik Imadatus Sa’adati; Imron Muzakki (UIN Sunan Gunung Djati Bandung, 2023)
Nowadays, street children are found everywhere, especially in public places. These street children often perform behavior that disturbs the community. One of the behaviors that is often carried out is aggressive behavior, both physical and verbal aggression. The purpose of this study was to determine aggressive behavior on street children in Bandung. The method used is descriptive method with the characteristics of the respondents, namely male street children aged 13-18 years and included in the classification of